1998
DOI: 10.1103/physrevb.58.10835
|View full text |Cite
|
Sign up to set email alerts
|

Surface-tip interactions in noncontact atomic-force microscopy on reactive surfaces: Si(111)

Abstract: Total-energy pseudopotential calculations are used to study the imaging process in noncontact atomic-force microscopy on Si͑111͒ surfaces. At the distance of closest approach between the tip and the surface, there is an onset of covalent chemical bonding between the dangling bonds of the tip and the surface. Displacement curves and lateral scans on the surface show that this interaction energy and force are comparable to the macroscopic Van der Waals interaction. However, the covalent interaction completely do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
175
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 39 publications
15
175
1
Order By: Relevance
“…To summarize, we have shown that using dangling bond terminated Si tips offers an opportunity for chemically resolved imaging of the CaF 2 , Al 2 O 3 , TiO 2 , and MgO surfaces due to stronger interaction with the surface anions. Similar results have been obtained for the insulating CaCO 3 10 1 14 surface [19] and semiconductor surfaces Si(111) [16], GaAs(110), and InP(110) [7] with the contrast mechanism in images predicted to be due to the formation of covalent bonds between the tip apex and the surface. For binary semiconductors this is also always strongest over anions in the surface, suggesting that with reactive silicon tips, the source of contrast in images on semiconductors and insulators is immediately evident.…”
Section: -3supporting
confidence: 69%
See 1 more Smart Citation
“…To summarize, we have shown that using dangling bond terminated Si tips offers an opportunity for chemically resolved imaging of the CaF 2 , Al 2 O 3 , TiO 2 , and MgO surfaces due to stronger interaction with the surface anions. Similar results have been obtained for the insulating CaCO 3 10 1 14 surface [19] and semiconductor surfaces Si(111) [16], GaAs(110), and InP(110) [7] with the contrast mechanism in images predicted to be due to the formation of covalent bonds between the tip apex and the surface. For binary semiconductors this is also always strongest over anions in the surface, suggesting that with reactive silicon tips, the source of contrast in images on semiconductors and insulators is immediately evident.…”
Section: -3supporting
confidence: 69%
“…However, the ground-state properties of these systems are well reproduced in DFT, so this error does not affect our conclusions. The silicon tip used in this study consists of a ten-atom silicon cluster with a single dangling bond at the apex and its base terminated by hydrogen [16]. The one-electron state of the dangling bond is split from other occupied states of the Si tip modeling the Si valence band.…”
mentioning
confidence: 99%
“…The parameters for the Morse potential are chosen as proposed for silicon by Pérez et al 16 The resulting potential curve is shown in the red solid graph in Fig. 1͑a͒.…”
Section: Repulsive Interactionsmentioning
confidence: 99%
“…In the simulations of this work, the surface was mimicked using a repeated slab geometry with four layers of silicon (the lowest of them saturated with hydrogen atoms). Two tips were considered: the first was a tungsten bcc pyramid pointing in the (111) direction, with 20 atoms; the second tip was made of ten silicon atoms [15], in which all dangling-bonds were saturated with hydrogen atoms except that of the apex. The wave-functions of the surface and tips were calculated within DFT in its local density approximation [16] (LDA), using the S code [17,18].…”
Section: The Cits Maps Of ∂I(x Y V)/∂v Are Obtained From I(x Y V)mentioning
confidence: 99%